Determining the inherent selectivity for carbon radical hydroxylation versus halogenation with high-spin oxoiron(iv)–halide complexes: a concerted rebound step. Issue 16 (29th March 2022) - Tao, Yaping; Li, Zixian; Zhang, Yiman; Sun, kexi; Liu, Zhaojun
Abstract : DFT calculation for the hydroxylation versus halogenation of propylene by [Fe IV (O)(TQA)X] + (X = F, Cl and Br) reveals that after hydrogen abstraction, halogen and oxygen rebound reactions are a synergistic process. Abstract : A synthetic iron model can process both halogenation and hydroxylation with vague selectivity, which is different from halogenase even though these structures are used for the simulation of halogenase. The key factor of the synthetic oxo-iron model mediated hydroxylation or the halogenation is still under debate. Herein density functional theory calculation is used to investigate the hydroxylation versus halogenation of propylene by the complex [Fe IV (O)(TQA)(X)] + (X = F, Cl, Br). Our results suggest that a concerted rebound mechanism (between the -X and the hydroxyl ligands after the hydrogen abstraction) leads to the formation of two different kinds of products.